LITERATURE REVIEW: IMPLEMENTATION AND BENEFITS OF ENVIRONMENTAL ACCOUNTING - Oematan, Desni Mariani; Kartini, Sisilia; Alves, Olinda Da Cruz (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study presents an in-depth review of the implementation and benefits of environmental accounting through a qualitative literature study approach. Using text analysis methods, this research explores recent developments in environmental accounting practices and their impact on organizational sustainability and performance. The analysis identifies patterns and trends in related research, providing a better understanding of how environmental accounting can be applied and yield significant benefits for companies. The findings highlight the importance of transparent and accountable environmental information disclosure to enhance stakeholder trust and strengthen corporate reputation. This study also delves into the practical and theoretical implications of implementing environmental accounting in the context of evolving regulations and societal demands for corporate social responsibility. This research makes a significant contribution to the environmental accounting literature by identifying the challenges and opportunities in adopting sustainable and environmentally responsive accounting practices.